2000
DOI: 10.1177/1077559500005004002
|View full text |Cite
|
Sign up to set email alerts
|

Dating Experiences of Bullies in Early Adolescence

Abstract: In this study, 196 young adolescents who reported that they bullied their peers were identified out of a sample of 1,758 students in Grades 5 through 8. After selecting from the total sample a group of nonbullying youth who were matched on gender, school, and grade, a comparison was made of the groups' dating experiences, quality of friend and boyfriend or girlfriend relationships, and acts of physical and social aggression. The results indicated that bullies started dating earlier and engaged in more advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
3
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(184 citation statements)
references
References 32 publications
12
162
3
7
Order By: Relevance
“…Marvell and Moody (1999) found that men who were violent to their female partners typically had prior criminal records. Connolly et al (2000) found that adolescents who reported bullying their peers at school were more likely to report physical aggression to their partners. Thornton, Graham-Kevan, and Archer (2010) found that IPV and general violence showed moderate associations for both sexes in a student sample.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Marvell and Moody (1999) found that men who were violent to their female partners typically had prior criminal records. Connolly et al (2000) found that adolescents who reported bullying their peers at school were more likely to report physical aggression to their partners. Thornton, Graham-Kevan, and Archer (2010) found that IPV and general violence showed moderate associations for both sexes in a student sample.…”
Section: Discussionmentioning
confidence: 97%
“…Two further assumptions are that such values produce attitudes supportive of men's violence to women, and that IPV should be studied independently of general aggression research, since general models of aggression do not characterize this form of violence (e.g., Browne, 1987). In particular, men's control is viewed as resulting from patriarchal values (e.g., Dobash & Dobash, 1979) rather than as part of an interpersonal style that can exist in either sex (e.g., Connolly, Pepler, Craig, & Taradash, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The social position and quality of peer relations may also be reflected in bullies' romantic relationships and their sexual behaviour. Bullies seem to start dating earlier and participate in more advanced forms of dating, but their relationships also tend to be less supportive and more violent relationships [45]. It may be that girls who bully others have learnt that aggression is a way of forming interpersonal relations.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that bullies are more willing to have a child than their non-bullying peers. A study by Connolly et al [45], suggested that bullies are prepared to engage in undesirable activities to keep their partners and consider their relationships very important. The desire for intimacy may also be related to positive attitudes toward parenthood.…”
Section: Discussionmentioning
confidence: 99%
“…Th is phenomenon can even be found in the United States, particularly among gangs, in which the most violent gang members often have the highest status (Campbell, 1993) and the most sexual partners (Buss, 2011;Ghiglieri, 1999;Palmer & Tilly, 1995). Even among children and adolescents who do not engage in criminal behavior, the (Vaillancourt, Hymel, & McDougall, 2003), resources ranging from lunch money and books to leather jackets and designer sneakers (Buss, 2011;Olweus, 1978), and dating or mating opportunities (Connolly, Pepler, Craig, & Taradash, 2000). Th e importance that men place on status, and perceived threats to one's status, makes sense when we consider the small groups in which humans lived for the majority of our evolutionary history.…”
Section: In the Name Of Lovementioning
confidence: 99%